Combined Body Weight, Abdominal Strengthening and Breathing Exercise for Post COVID LSCS Women - Dasarapu, Indrani; Jagatheesan, Alagesan; Prathap, Suganthirababu; Dubba, NagaRaju; Vinosh Kumar, Purushothaman (INTI International University, 2022)
Background: The Respiratory Syndrome (SARS) family and some strains of the common cold are related by the SARS-coV-2 virus, a novel virus. For mothers who underwent a post-lower segment Caesarean section, post-COVID disorders like fatigue, dyspnea, arthromyalgia, depression and insomnia have severe repercussions, and caring for their newborn would be difficult. Objective: The aim of this study was to investigate the impact of combined body weight, abdominal strengthening and breathing exercise for Post COVID Lower Segment Caesarean Section Women. Methods: A double-blinded pilot randomized controlled trial was conducted on 30 subjects who underwent post Lower Segment Caesarean Section. Subjects were divided into 2 groups with 15 subjects in each group. Group-A received breathing exercises, abdominal draw-in maneuver, upper limb and lower limb strengthening exercises. Group-B was treated with straight plank, elbow plank, hip twist, crunch kicks, hollow body hold, combined with abdominal draw-in manoeuvre and breathing exercise. Results: Statistical analyses of post-test values of ultrasonography, dynamometer, and sit-up tests revealed that patients who received combined body weight, abdominal strengthening, and breathing exercises in Group B showed significant improvement as compared to post-COVID LSCS women who received only breathing exercises, abdominal draw-in maneuver, and upper and lower limb strengthening exercises in Group A. Conclusion: The study concluded that the combined body weight, abdominal strengthening and breathing exercise was effective in treating for Post COVID Lower Segment Caesarean Section women.